REFORMULASI KEPEMIMPINAN PENDIDIKAN ISLAM DI ERA REVOLUSI INDUSTRI 4.0 - Sutrimo Purnomo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
This article aims to provide an alternative solution to the world of education in the form of reformulation of Islamic education leadership in the industrial revolution 4.0. Industrial Revolution Era 4.0 is an era marked by the existence of a digital revolution that is a combination of various technologies that blur the lines of physical, digital and biological space. This era has implications for the increasingly sparse space and time and physical activity and communication at a geographical location. Everything changed from a manual to a digital one which turned out to have a significant impact on various lines of people's lives, including in the world of education. If the leadership of Islamic education is unwilling and able to adapt to this era, then Islamic education will be increasingly left behind. For this reason, it is necessary to reformulate Islamic educational leadership, namely through disruptive mindset, self-driving, and reshape or create steps. With these steps the leaders of Islamic education will be able to provide breakthroughs for the development of Islamic education and provide a guarantee of satisfaction for its users. The reformulation of Islamic education leadership also needs to be supported by strengthening users, strengthening strategies, and strengthening information and communication technology based on Islamic and applicable values ​​so that Islamic education is able to answer the hopes and needs of the community, not again limited to education that is sky-high but grounded education.